Pronosticos AClimateColombia: A system for the provision of information for climate risk reduction in Colombia - Sotelo, Steven; Guevara, Edward D.; Llanos Herrera, Lizeth; Agudelo, Diego; Esquivel, Alejandra; Rodríguez, Jefferson; Ordoñez, Leonardo; Mesa, Jeison; Muñoz Borja, Luis Armando; Howland, Fanny C.; Amariles, Sebastian; Rojas, Alexander; et al. (Elsevier, 2020)
Climate variability poses major risks to agricultural production around the world, including in Colombia. Despite progress, major gaps still exist for the continuous provision of climate services for the Colombian agricultural sector. These gaps include lack of capacities in farming communities and technical assistants to understand and use seasonal forecast information, as well as the systematic provision of agro-climatic information. Here, we describe a user-centered digital agro-climatic forecast system that addresses several of these gaps. The system, named, “Pronosticos AClimateColombia,” and available at https://pronosticos.aclimatecolombia.org, formalizes the processing of climate and crop information from quality control, forecasting, and tailoring to crop-specific decision-making processes. The design, development and evaluation process captured user needs through regular engagement with key stakeholders ranging from the Ministry of Agriculture, the National Meteorological Service (IDEAM), as well as farmer organizations and farmers in a range of agricultural areas. We describe the process of design, testing and deployment of the system, in which forecast generation is performed as a series of automated steps, with agro-climatic forecasts issued on the 7th day of every month with a rolling lead-time of six months. We show that the constant gathering of user requirements and feedback resulted in users expressing substantial interest in using the system, though with some limitations on the level of understanding of the provided information. The limitations indicate a need for improved capacity at the local level. This underscores the importance of cyclical, continuous, feedback and discussion processes for climate services.